The role of self-organization theory in the development of students’ interdisciplinary research ability - Mukushev, Bazarbek; Bazarbekova, Aizhan; Ibatayev, Zharkyn; Sydykova, Zhainagul; Mukushev, Serik (Institute of Advanced Engineering and Science, 2024)
Self-organization theory is an interdisciplinary scientific direction to improve the quality of acquired knowledge and skills. The article aims to study the development of interdisciplinary research activities among students based on self-organization theory. The study was conducted using an integrated approach, methods of analysis and synthesis, modeling, pedagogical experiments, and mathematical statistics. An elective course, “synergetic-interdisciplinary scientific theory”, and a model for preparing students for interdisciplinary research activities were developed and implemented. The knowledge and skills of 272 physics students in the Republic of Kazakhstan universities in control and experimental groups improved after the training. The knowledge highest level is observed among the experimental group students while studying the natural experiments’ theoretical aspects necessary for researching the natural objects’ sustainability. Experimental group students demonstrated better results in completing the task based on the acquired knowledge and skills. They rated the education quality significantly better on a short educational assessment scale. The results-developed course and the students’ preparing models for interdisciplinary research can be used in advanced courses for different specialties educators. Research perspectives could potentially contribute to the development of integrated subjects and interdisciplinary programs in natural sciences and humanities.